Postura argentina ante el conflicto en Gaza - Botta, Paulo (El Colegio de México A.C., 2024)
Argentina’s position to the recent conflict in Israel and the Gaza Strip stands apart from that of other Ibero-American nations, intertwining with three distinct factors since October 7th. Firstly, the fact that Argentine citizens were among those affected by the violence perpetrated by terrorist groups. Secondly, these events unfolded amidst a highly polarized electoral process and a change in the administration. Thirdly, the rise of President Javier Milei, who has openly expressed support for Israel.